Can Religious Affiliation Explain the Disadvantage of Muslim Women in the British Labour Market?. (December 2018) - Khattab, Nabil; Hussein, Shereen
This article aims to explain the labour market penalties among Muslim women in Britain. It draws on theories of intersectionality and colour/cultural racism to argue that the labour market experience of British-Muslim women is multiply determined via criteria of ascription such as ethnicity, migration status, race and religion rather than criteria of achievement. The study uses data from the Labour Force Survey (2002–2013) with a large sample (N=245, 391) of women aged 19–65 years. The overarching finding suggests that most Muslim women, regardless of their multiple ascriptive identities, generation and levels of qualifications, still face significant penalties compared with their White-British Christian counterparts. The penalties for some groups, such as Pakistani, Bangladeshi and Black-Muslim women, are harsher than for Indian and White-Muslim women, demonstrating how different social markers and multiple identities have contingent relationships to multiple determinants and outcomes.